Answer:
The mass of the earth, ![M=6.023\times 10^{24}\ kg](https://tex.z-dn.net/?f=M%3D6.023%5Ctimes%2010%5E%7B24%7D%5C%20kg)
Explanation:
It is given that,
Time taken by the moon to orbit the earth, ![T=27.3\ days=2358720\ m](https://tex.z-dn.net/?f=T%3D27.3%5C%20days%3D2358720%5C%20m)
Distance between moon and the earth,
We need to find the mass of the Earth using Kepler's third law of motion as :
![T^2=\dfrac{4\pi^2}{GM}r^3](https://tex.z-dn.net/?f=T%5E2%3D%5Cdfrac%7B4%5Cpi%5E2%7D%7BGM%7Dr%5E3)
![M=\dfrac{4\pi^2r^3}{T^2G}](https://tex.z-dn.net/?f=M%3D%5Cdfrac%7B4%5Cpi%5E2r%5E3%7D%7BT%5E2G%7D)
![M=\dfrac{4\pi^2\times (384\times 10^6)^3}{(2358720)^2\times 6.67\times 10^{-11}}](https://tex.z-dn.net/?f=M%3D%5Cdfrac%7B4%5Cpi%5E2%5Ctimes%20%28384%5Ctimes%2010%5E6%29%5E3%7D%7B%282358720%29%5E2%5Ctimes%206.67%5Ctimes%2010%5E%7B-11%7D%7D)
![M=6.023\times 10^{24}\ kg](https://tex.z-dn.net/?f=M%3D6.023%5Ctimes%2010%5E%7B24%7D%5C%20kg)
So, the mass of the earth is
. Hence, this is the required solution.
Answer:
a)
Y0 = 0 m
Vy0 = 15 m/s
ay = -9.81 m/s^2
b) 7.71 m
c) 3.06 s
Explanation:
The knowns are that the initial vertical speed (at t = 0 s) is 15 m/s upwards. Also at that time the dolphin is coming out of the water, so its initial position is 0 m. And since we can safely assume this happens in Earth, the acceleration is the acceleration of gravity, which is 9.81 m/s^2 pointing downwards
Y(0) = 0 m
Vy(0) = 15 m/s
ay = -9.81 m/s^2 (negative because it points down)
Since acceleration is constant we can use the equation for uniformly accelerated movement:
Y(t) = Y0 + Vy0 * t + 1/2 * a * t^2
To find the highest point we do the first time derivative (this is the speed:
V(t) = Vy0 + a * t
We equate this to zero
0 = Vy0 + a * t
0 = 15 - 9.81 * t
15 = 9.81 * t
t = 0.654 s
At this time it will have a height of:
Y(0.654) = 0 + 15 * 0.654 - 1/2 * 9.81 * 0.654^2 = 7.71 m
The doplhin jumps and falls back into the water, when it falls again it position will be 0 again. So we can equate the position to zero to find how long it was in the air knowing that it started the jump at t = 0s.
0 = Y0 + Vy0 * t + 1/2 * a * t^2
0 = 0 + 15 * t - 1/2 * 9.81 t^2
0 = 15 * t - 4.9 * t^2
0 = t * (15 - 4.9 * t)
t1 = 0 This is the moment it jumped into the air
0 = 15 - 4.9 * t2
15 = 4.9 * t2
t2 = 3.06 s This is the moment when it falls again.
3.06 - 0 = 3.06 s
<em><u>throwing a ball up initially has a lot of kinetic energy because it is moving upwards ( kinetic energy is energy which a body possesses by virtue of being in motion.) this all then get converted to gravitational potential energy, and for a moment it is stationary before it begins to fall again. by the time it has returned again, all the gravitational potential energy has turned back into kinetic.</u></em>
<span>the statement that is true regarding flexibility is : b. a joint's range of motion will be lost if the joint is not used regularly.
Our body is like a machine. If we not constantly heat it up, our body will be more prone to injury. We can see that the old people who lived within the tribe in the middle of the mountain are far stronger than the one who lived in the city.</span>
Answer:
2
Explanation:
To find force it's force = mass times acceleration so to find mass you would divide force by acceleration